Facies Analysis and Depositional Environment of Garagu Formation (Valanginian- Hauterivian) in Gara Mountain, Gali Garagu, Sarsang District, Iraqi Kurdistan Region - Balaky, Sardar M.; Abdula, Rzger A.; Perot, Edres M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Facies analysis and depositional environment of Garagu Formation (Valanginian- Hauterivian) in the Gara Mountain in Gali Garagu of High Folded Zone, Sarsang District, and northern Iraqi Kurdistan is studied. Lithologically, the formation consists of oolitic sandy limestones, with shale, marl and sandstones in its upper and lower parts and organic detrital limestones in its middle part. The petrographic study of carbonate rocks on 30 thin sections shows that the limestones are dominated by mudstones and wackestones.The skeletal grains include variety of benthic foraminiferas, gastropods, brachiopods, echinoids, pelecypods, green algae, and ostracods. Non-skeletal grains include ooids, peloids and intraclasts. Garagu sandstones are immature, lithic subarkose to subarkose and occur as medium to thick beds within the lower and upper parts of the formation, and composed mainly of sedimentary rock fragments with minor amount of quartz and feldspars (plagioclase). The X-ray diffraction analysis of the bulk shale samples revealed that the abundant clay mineral in Garagu Formation is kaolinite and non-clay minerals include calcite, quartz, geothite and nacirite. The formation can be divided into three lithologic devisions from base to top: lower oolitic; middle organic detrital limestone; and upper oolitic. Eight different microfacies were recognized which were subdivided according to their environmental interpretation into two basic types of facies associations; shelf margin (shoal) and shelf lagoon association. Generally the Garagu Formation represents shallow water environment with two high energy belts in the lower and upper parts.
Keywords: FaciesCarbonateGaraguLagoonGara MountainKurdistan